Genetic analysis of mutations that compensate for loss of Escherichia coli DNA topoisomerase I. - Raji, A (1985)
A transposon Tn10 insertion in topA, the structural gene of Escherichia coli DNA topoisomerase I, behaves as an excluded marker in genetic crosses with many strains of E. coli. However, derivative strains that accept this mutant topA allele are readily selected. We show that many of these topA mutant strains contain additional mutations that compensate for the loss of DNA topoisomerase I. Genetic methods for mapping and manipulating such compensatory mutations are described. These methods include a plate-mating test for the ability of strains to accept a topA::Tn10 allele and a powerful indirect selection for transferring compensatory mutations from male strains into non-compensatory female strains. One collection of spontaneous compensatory mutants is analyzed in detail and is shown to include compensatory mutations at three distinct loci: gyrA and gyrB, the genes that encode the subunits of DNA gyrase, and a previously unidentified locus near tolC. Mutations at this third locus, referred to as toc (topoisomerase one compensatory) mutations, do not behave as point mutations in transductional crosses and do not result in lowered DNA gyrase activity. These results show that wild-type strains of E. coli require DNA topoisomerase I, and at least one class of compensatory mutations can relieve this requirement by a mechanism other than reduction of DNA gyrase activity.